The Influence of CAMEL Ratio on Bank Stock Price Changes Post COVID-19 - Dasuki, Havid; Suripto, Suripto; Wardianto, Kussuyatmono Bagus (The Eastasouth Journal of Social Science and Humanities, 2025)
The purpose of this study is to empirically test the effect of CAMEL on changes in stock prices after COVID-19 in banking companies listed on the Indonesia Stock Exchange. This study is descriptive explanatory with a quantitative approach. Analysis with data processing using the EViews program. The results of the study indicate that CAR has no significant effect on changes in stock prices, RORA has a significant effect and has a negative relationship direction on changes in stock prices, NPM has no significant effect on changes in stock prices, ROA has a significant effect and has a positive relationship direction on changes in stock prices, and LDR has no significant effect on changes in stock prices.